On Spectrum of Differential Operator with Block-Triangular Matrix Coefficients - Kholkin, A.M.; Rofe-Beketov, F.S. (Журнал математической физики, анализа, геометрии, 2014)
For the Sturm-Louville equation with block-triangular matrix potential that increases at infinity, both increasing and decreasing at infinity matrix solutions are found. The structure of spectrum for the differential operator with these coefficients is defined. Для уравнения Штурма-Лиувилля с блочно-треугольным растущим на бесконечности матричным потенциалом построены убывающие и растущие на бесконечности матричные решения. Установлена структура спектра дифференциального оператора с такими коэффициентами.